Influence of environmental performance and green accounting on the financial performance of manufacturing companies from the maqashid syari'ah perspective - Ningrum, Anjar Puspa; Sari, Yetri Martika; Ermawati, Liya (Junal Ilmu Manajemen, 2024)
The aim of this research is to find out how the influence of environmental performance and green accounting affects the financial performance of manufacturing companies partially and simultaneously, studying companies listed on the Indonesia Stock Exchange for the 2018-2023 period. Purposive sampling is the method used in this investigation. Using the E-Views 10 program, panel data regression analysis is a display of the data used and secondary data sources from annual financial reports and literature related to the topic for collecting data. Research findings show that in particular, environmental performance has a negative and significant influence on audit quality, green accounting has a positive and significant influence on the financial performance of manufacturing companies. Simultaneously, environmental performance and green accounting together have a significant impact on audit quality.